2000
DOI: 10.1021/jf0006832
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenols Inhibit the Sodium-Dependent Glucose Transporter of Intestinal Epithelial Cells by a Competitive Mechanism

Abstract: Intestinal glucose uptake is mainly performed by the sodium-dependent glucose transporter, SGLT1. The transport activity of SGLT1 was markedly inhibited by green tea polyphenols, this inhibitory activity being most pronounced in polyphenols having galloyl residues such as epicatechin gallate (ECg) and epigallocatechin gallate (EGCg). Experiments using brush-border membrane vesicles obtained from the rabbit small intestine demonstrated that ECg inhibited SGLT1 in a competitive manner, although ECg itself was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
239
3
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(263 citation statements)
references
References 27 publications
16
239
3
5
Order By: Relevance
“…So, we know that coffee contains many compounds, which may have potential to influence glucose metabolism process to prevent hyperglycemia and oxidative stress consequently. For instance, chlorogenic acid inhibits glucose transporters (Na þ -dependent glucose transporter) (Kobayashi et al, 2000). Chlorogenic acid also reduces or inhibits glucose-6-phosphatase (Glc-6-phase) hydrolysis, which may reduce plasma glucose output from the liver, leading to reduced plasma glucose concentration (Newgard et al, 1984;Arion et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…So, we know that coffee contains many compounds, which may have potential to influence glucose metabolism process to prevent hyperglycemia and oxidative stress consequently. For instance, chlorogenic acid inhibits glucose transporters (Na þ -dependent glucose transporter) (Kobayashi et al, 2000). Chlorogenic acid also reduces or inhibits glucose-6-phosphatase (Glc-6-phase) hydrolysis, which may reduce plasma glucose output from the liver, leading to reduced plasma glucose concentration (Newgard et al, 1984;Arion et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…29 On the other hand, it has also been reported that tea catechins including EGCG could inhibit the sodiumdependent glucose transporter. 30 If the reduced energy absorption is taken into account, EGCG resulted in a slightly (but not significantly) reduced total energy digestion of about 200 kJ throughout the 4-week treatment period (control: 2790 kJ, EGCG 0.5%: 2565 kJ, EGCG 1%: 2587 kJ). In total, 200 kJ correspond to the energy content of approximately 5 g lipids, which is very close to the difference in body fat gain between the control group and the 1% EGCG group.…”
Section: Egcg Prevents Obesity S Klaus Et Almentioning
confidence: 93%
“…It was shown that green tea treatment of diabetic rats significantly reduced the blood glucose level. This antihyperglycemic effect may be linked to enhanced basal and insulin-stimulated glucose uptake in rat adipocytes [139], inhibition of the intestinal glucose transporter [140], and decreased expression of genes that control gluconeogenesis [141]. Green tea supplementation also reduced the accumulation of AGEs in diabetic rats as indicated by decreased collagen linked fluorescence [49].…”
Section: E (+)-Catechin (−)-Catechin (+)-Epicatechin and (−)-Epicmentioning
confidence: 99%